White Oak Dance Project Review - Craine, Debra (Dance Books Ltd., Alton,Hampshire (UK), 2001)
PALABRAS CLAVE: White Oak Dance Project, PastForward, Mikhail Baryshnikov, Yvonne Rainer, Steve Paxton, Satisfyin Lover, Flat.
Dentro del apartado "Dance Now. Highland Fling. Edinburgh Festival 2001".